Self-differentiation and parenting stress in adolescent mothers. An exploratory study - Salerno, Alessandra; Tosto, Monica; Raciti, Iolanda; Merenda, Aluette (Frontiers in Developmental Psychology, 2024)
Introduction. Adolescent motherhood, a phenomenon with a strong social impact, has been explored and has particularly focused on the mother's psychosocial development, parental role, skill and parenting-related stress. Methods. This study aims to analyze the connection between the maternal Self-differentiation in first-time mothers (aged between 15 and 20 years old) and Parenting Stress levels, including some moderating variables such as: the dyadic adjustment, maternal self-esteem and the perceived social support. Results. The analyzes highlighted the following significant results: 1) EC and FO are predictors of the Parenting Stress (respectively, X 3 : β = -.38 with ρ < .05; X 4 : β = .36, with ρ = .05); EC has also been found to be a significant predictor of P-CDI (β = -.42 with ρ < .05), while FO predicts DC (β = .39, with ρ < .05); a predictive effect of the Positive self-worth subdimension on Difficult Child has been found (β = -.37; ρ < .05); a predictive effects of Dyadic Cohesion on DC (β = -.40; ρ < .05). Discussion: The results are discussed within a socio-cultural perspective, and considering their implications on early motherhood, especially in Italy.